(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of multifunctions called upper nearly (τ_1,τ_2)-continuous multifunctions and lower nearly (τ_1,τ_2)-continuous multifunctions. Furthermore, some characterizations of upper nearly (τ_1,τ_2)-continuous multifunctions and lower nearly (τ_1,τ_2)-continuous multifunctions are established.